Does Improving Sleep Patterns Modify Insulin Resistance In Patients With Type 2 Diabetes? : A Systematic Review - I Komang Swardika; I Wayan Eri Purnama Yuda (International Medical Journal Corp. Ltd, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and hyperglycemia. Emerging research highlights the bidirectional relationship between sleep disturbances and metabolic health, suggesting that improving sleep patterns may mitigate insulin resistance in T2DM patients. This systematic review evaluates the effectiveness of sleep interventions in modifying insulin resistance. Methods: Adhering to PRISMA 2020 guidelines, this study screened randomized controlled trials, quasi-experimental studies, and systematic reviews from databases like PubMed, Springer, and Google Scholar. Inclusion criteria focused on adults with T2DM, sleep interventions (e.g., cognitive behavioral therapy for insomnia [CBT-I], sleep hygiene, pharmacological agents), and outcomes measuring insulin resistance (e.g., HOMA-IR, HbA1c). Data extraction included study design, participant characteristics, intervention details, and metabolic outcomes. Results: Nineteen studies were included. Behavioral interventions, particularly CBT-I and sleep hygiene training, consistently improved sleep quality and insulin resistance markers, such as reductions in PSQI scores (-1.48) and HOMA-IR (-1.29). Pharmacological agents (e.g., melatonin, trazodone) enhanced sleep but showed inconsistent metabolic benefits. Longer-term interventions (up to 12 months) demonstrated more robust improvements compared to short-term approaches. Secondary benefits included better glycemic control, reduced blood pressure, and improved well-being. Discussion: Behavioral interventions were more effective than pharmacological ones in addressing both sleep and metabolic outcomes. The variability in results underscores the need for standardized protocols and larger trials. Limitations included small sample sizes and methodological heterogeneity. Conclusion: Improving sleep patterns, especially through CBT-I and sleep hygiene, can significantly reduce insulin resistance in T2DM patients. Integrating these interventions into diabetes management may offer holistic benefits, though further research is needed to optimize their efficacy.